2014
DOI: 10.3109/2000656x.2014.886582
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and early complications following reduction mammaplasty: An analysis of 4545 patients from the 2005–2011 NSQIP datasets

Abstract: Reduction mammoplasty is a proven treatment for symptomatic macromastia, but the association between obesity and early postoperative complications is unclear. The purpose of this study was to perform a population level analysis in an effort to determine the impact of obesity on early complications after reduction mammaplasty. This study examined the 2005-2011 NSQIP datasets and identified all patients who underwent reduction mammoplasty. Patients were then categorised according to the World Health Organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…There were three prospective studies while the others were retrospective ones. Mean postoperative follow-up time was noted in nine studies [6, 11, 15, 2126] and occurred from 1 to 32.9 months after surgery. Five studies [5, 1719, 27] did not report follow-up time, and the last two studies [14, 20] only reported a range.…”
Section: Resultsmentioning
confidence: 99%
“…There were three prospective studies while the others were retrospective ones. Mean postoperative follow-up time was noted in nine studies [6, 11, 15, 2126] and occurred from 1 to 32.9 months after surgery. Five studies [5, 1719, 27] did not report follow-up time, and the last two studies [14, 20] only reported a range.…”
Section: Resultsmentioning
confidence: 99%
“…[14,15,17] However, contradictory findings exist in the literature as well, supporting obesity as a risk factor. [6,[9][10][11][12][13] Chun et al [13] identified a threshold of BMI 35.6 at which postoperative complications were increased two-fold, the most common complication being infection. The pioneering study using NSQIP data to analyze BMI and breast reduction complications by Nelson et al [6] included 4,545 patients between 2005 and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Like other NSQIP-based analyses of reduction mammaplasty, there are limitations to this study. [6,27] Follow-up was only 30 days, a relatively short period of time. NSQIP does not include complications such as seroma, hematoma, fat necrosis, altered nipple sensation, aesthetic outcomes, or hypertrophic scarring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations